Musa cavendish ameliorates isoproterenol-induced renal and hepatic injury in Wistar rats: Effects of musa cavendish on isoproterenol induced derangements of renal and hepatic biochemistry - Umukoro, Emuesiri Kohworho; Akponah, Erhiori; Elijah, Oghenekparobor Blessing; Moke, Emuesiri Goodies; Ohaju-Obodo, John O.; Georgewill, Abraham (Orapuh Journal, 2025)
Introduction Isoproterenol (ISP) treatment is an established model for inducing myocardial infarction (MI). In acute MI, compromised renal function may result from preexisting kidney disease, acute renal failure, or the effects of pharmaceuticals and contrast agents used during diagnostic or therapeutic procedures, which are reflected by changes in biochemical indices. Purpose Musa cavendish (MC), commonly known as banana, is a staple food in many regions worldwide. MC has demonstrated ameliorative effects against hepato-renal damage caused by various pathologies. This study aimed to investigate the effects of Musa cavendish on isoproterenol-induced renal and hepatic injury in Wistar rats. Methods Wistar rats were divided into six groups. Groups 4 to 6 received MC at doses of 100, 200, and 400 mg/kg, respectively, for 30 days. Groups 2 to 6 were also administered ISP (85 mg/kg) on days 29 and 30. Results Results showed significant reductions in sodium, bicarbonate, and chloride levels, as well as elevations in urea and creatinine, which were reversed in the MC treatment groups. Additionally, increases in potassium, alkaline phosphatase (ALP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), albumin, and both direct and total bilirubin observed in the control groups were also reversed following MC treatment. Conclusion In conclusion, Musa cavendish ameliorates isoproterenol-induced renal and hepatic injury in Wistar rats.